2017
DOI: 10.1631/jzus.b1700180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets

Abstract: This study was conducted to investigate the effects of fresh fermented soybean meal (FSM) on the growth performance of nursery piglets, nitrogen excretion in feces, and the concentrations of ammonia (NH 3 ) and particulate matter (PM) in the piggery. A total of 472 nursery piglets (Landrace×Yorkshire, (16.3±0.36) kg body weight) were randomly allocated into two treatments with 236 pigs in each treatment. The pigs were fed the basal diet without fresh FSM (control) or diet containing 10% (100 g/kg) fresh FSM (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…TP and PUN are indicators for the overall metabolism of body proteins. Within a certain range, the higher the TP concentration, the stronger the body's ability to synthesize and utilize proteins [22]. PUN concentration, on the other hand, has been negatively correlated with N deposition rate and protein utilization and a reduction in PUN indicates an increase in N utilization efficiency or a decrease in protein decomposition [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP and PUN are indicators for the overall metabolism of body proteins. Within a certain range, the higher the TP concentration, the stronger the body's ability to synthesize and utilize proteins [22]. PUN concentration, on the other hand, has been negatively correlated with N deposition rate and protein utilization and a reduction in PUN indicates an increase in N utilization efficiency or a decrease in protein decomposition [23].…”
Section: Discussionmentioning
confidence: 99%
“…The feed consumption was measured every day to calculate the average daily feed intake (ADFI) and feed to gain ratio (F/G). Fresh fecal grab samples were collected in the morning during the last week (experimental d [21][22][23][24][25][26][27][28] and pooled by pen and stored at −20 • C for N and P emissions analysis. Each piglet was weighed at the end of the experiment, the two pigs closest to the average weight of treatments were selected from each replicate pen for slaughter.…”
Section: Sample Collection and Slaughter Proceduresmentioning
confidence: 99%
“…Koo et al [65] reported that the addition of fermented barley enhances weaner piglets' gut health and increases immune responses and gut bacteria composition. According to Cheng et al [66] and Xu et al [67], fermented soybean meal has a positive influence on the growth performance of weaned piglets. Furthermore, new compounds formed in feed during fermentation can increase the growth performance of weaned piglets and growing pigs [67].…”
Section: Piglets' Growth Performancementioning
confidence: 99%
“…This fermentation strategy leads to effective use of local stocks and reduced dependence on imported soya, as well as higher economical effectiveness. The reduction of ammonia by modifying dietary composition is considered economical and feasible [66]. The significant ammonia emission reduction noted with the biomodified rapeseed compared with extruded soya meal underscores the lower dependence on imported soya products.…”
Section: Influence Of Fermented Feed On Ammonia Emissionmentioning
confidence: 99%
“…In recent years, research on finding alternatives to antibiotics in feed and reducing feed costs has continually promoted the development of FF for probiotics (8). Using FF could improve the growth performance of nursery (9) and weaned piglets (10). Meanwhile, FF has also been observed to improve the growth performance of their progeny and decrease diarrhea incidence (11).…”
Section: Introductionmentioning
confidence: 99%